The relationship between self-confidence and attitude of emergency medical technicians towards family presence during resuscitation - Jaber Najafi; Neda Gilani; Hadi Hassankhani; Mansour Ghafourifard; Abbas Dadashzadeh; Mahnaz Zali (International Journal of Emergency Medicine)
Abstract Background Family presence during resuscitation is a controversial issue worldwide. The aim of this study was to investigate the self-confidence and attitudes of Emergency Medical Technicians (EMTs) towards family presence during resuscitation (FPDR). Methods In this cross-sectional study, a random sample of 252 EMTs were selected from 110 prehospital emergency centers. Two main questionnaires were used to collect data on the EMTs’ self-confidence and attitudes towards FPDR. Results The results showed that the EMTs’ attitudes towards FPDR were lower than the mean (43.69 ± 19.40). In addition, more than 85% of them stated that the resuscitation process was stressful for the patient’s companions. There was a positive correlation between EMTs’ self-confidence and attitudes towards FPDR (r = 0.52, p < 0.01). The results showed that the smaller number of family members present during resuscitation was associated with higher EMTs’ self-confidence and more positive attitudes towards FPDR. Moreover, personnel with more experience, liability insurance, and advanced resuscitation training were significantly more self-confident than other personnel. Conclusion A large number of the EMS personnel have a negative attitude towards FPDR, but EMTs, with higher self-confidence, have a more positive attitude. Therefore, it is possible to improve the EMTs attitudes towards FPDR and increase their self-confidence by training them to perform resuscitation in the presence of the family and by preventing people from gathering at resuscitation scenes.